Analisis Yuridis Tindak Pidana Pelecehan Seksual Terhadap Anak Sebagai Korban Ditinjau dari Undang-Undang Nomor 35 Tahun 2014 Tentang Perubahan atas Undang-Undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak (Studi Putusan Nomor 6/PID/SUS-ANAK/2024/PNJKT - Sagala , Veronika; Sadat, Anwar (Postulat, 2025)
This study aims to analyze the criminal act of sexual abuse against minors under 18 years of age in review of Law Number 35 of 2014 is a regulation that amends Law Number 23 of 2002 concerning child protection with a case review based on verdict number 6/PID/SUS-ANAK/2024/PNJkt.Brt. The method used is Normative juridical with data analysis from books, articles or journals, laws and regulations and other sources. The results showed that the implementation of the Law on Child Protection is still faced with a gap between regulation and practice as also experienced by the victim in decision number 6/PID/SUS-ANAK/2024/PNJkt.Brt. The verdict shows that there is still a lack of and limited psychological support such as the provision of rehabilitation and recovery of victims through psycho social which the state is unable to fulfill. As a result, this research recommends the need to increase public awareness and strengthen the legal system to protect children from sexual crimes.